Professional learning and development needs of Chinese university-based physical education teacher educators - Gong, Yueying; MacPhail, Ann; Guberman, Ainat (European journal of teacher education, 2023)
This study examines the professional learning and development (PLD) needs of Chinese university-based physical education teacher educators (PETEds) and their views about effective ways to address them. This is significant given the limited research exploring this group. A European-wide survey was translated and distributed in China, receiving 251 responses of PETEds from 28 provinces. We found that the majority of PETEds had a strong desire to undertake further PLD in three areas: subject knowledge and didactics with particular emphasis on professional training in specific types of sports, research related academic activities and institutional activities. They preferred formal learning programmes as well as international learning activities to address these needs. The cost of the activities was the most significant factor influencing their engagement. We recommend paying closer attention to the PLD needs of specific subject area groups of teacher educators.